Collagen Biosynthesis in Osteoblast Cells Treated with Fish Collagen Peptides - Hema, G. S.; Shyni, K.; Prasad, M. Manu; Ninan, George; Mathew, Suseela (Fishery Technology, 2017)
Collagen is one of the most widely used biomaterialsin tissue engineering and regenerative medicine. Toinvestigate the effect of fish collagen peptides on theformation of collagen proteins by mature osteoblastcells, human osteoblast cells were treated withcollagen peptide in both time and dose dependentmanner. The stimulatory effect of collagen peptidewas confirmed by western blot and immunocytochemistryanalysis. The results clearly indicate thatthe presence of fish collagen peptides led to a dosedependent increase in collagen synthesis by osteoblastcells upto a concentration of 0.6 mg ml-1.However native collagen or collagen free proteinhydrolysate failed to stimulate the production ofcollagen in osteoblast cells. The results show astimulatory effect of fish collagen peptides on thecollagen biosynthesis in osteoblast cells and suggesta possible mechanism for the regulation of collagenturnover in joint tissues.